Coaching Parents of Young Children with Autism in Rural Areas Using Internet-Based Technologies: A Pilot Program. (September 2013) - Meadan, Hedda; Meyer, Lori E.; Snodgrass, Melinda R.; Halle, James W.
The purpose of this paper is to describe a pilot program (i.e., Internet-Based Parent-Implemented Communication Strategies [i-PiCS] program) that provides long-distance training and coaching via the Internet to parents of young children with autism spectrum disorders (ASD). The i-PiCS program is designed to teach parents how to use evidence-based teaching strategies to improve the social communication skills of their children with ASD. We describe components of a parent-training program that capitalizes on evidence-based strategies and highlights the potential for delivering this program via the Internet. Potential barriers, benefits, and implications for practice and research are discussed.